Overview of Biomass Hydrothermal Techniques for Carbon Quantum Dots Synthesis: Mini Review - Salim, La Ode Agus; Irwan, Irwan (Asian Journal of Environmental Research, 2024)
The aim of this study is to provide a comprehensive overview of various biomass hydrothermal techniques used in the synthesis of carbon quantum dots (CQDs), as well as to identify recent developments in this field. Careful literature search methods were employed to gather information related to biomass hydrothermal techniques and CQD synthesis, applying inclusion and exclusion criteria to select articles that align with the research focus. Data analysis approaches were used to organize and present relevant information. The main findings of this review encompass a range of hydrothermal techniques used in CQD synthesis, including diverse biomass feedstocks and process parameters influencing the final outcomes. Furthermore, the review also reveals recent advancements in CQD applications, such as in photocatalysis, biomedicine, and optoelectronics. The findings of this review have significant implications for further development in CQD synthesis using biomass hydrothermal techniques, with the potential application of this technology in various high-tech fields, including renewable energy, biomedicine, and sensing. Overall, this review provides an in-depth understanding of recent advancements in biomass hydrothermal techniques for CQD synthesis, highlighting the substantial potential of this research in supporting innovation across various application domains.